Implementasi Keterampilan Dasar Konseling dengan Helping Skill untuk Membantu Penyesuaian Gaya Belajar Pada Anak - Munir, Misbahul; Kusumadewi, Arhani Putri; Kurnia, Desi Ayu; Afifah, Firnanda Putri (Jurusan Bimbingan dan Konseling Islam, 2023)
Guidance and counseling services are counselors' efforts to shape students into individuals who develop optimally, are productive and can learn according to their characteristics. The purpose of this article is to provide information about how a counselor with good helping skills can solve the problems of clients, namely by introducing learning styles which are expected so that students can adapt learning styles that are suitable for the continuation of learning. The method used in this research is library research with data collection techniques using documentation techniques in the form of articles and books as references related to the topics discussed. The results of the analysis obtained are that the basic skills possessed by counselors through helping skills can help adjust students' learning styles through approaches to find out the right characteristics and strategies.